Self-governing prisons: Prison gangs in an international perspective - Butler, Michelle (Trends in organized crime, 2022)
This paper finds qualified support for the use of Skarbek’s (2011, 2014) governance theory to understand the emergence of prison gang-like groups in Kyrgyzstan, Northern Ireland and Brazil. However, Skarbek’s (2011, 2014) governance theory has little to say about how many prison gangs emerge and how they organise comparatively outside the US context. This paper argues that variation in the number of gangs and their monopolization of informal governance can only be explained by considering importation and deprivation theories alongside governance theories. These theories factor in variation in prison environments and pre-existing societal divisions imported into prison, which affect the costs on information transmission and incentives for gang expansion. In particular, the paper pays attention to the wider role social and political processes play in influencing whether monopoly power by prison gangs is supported and legitimized or not.